An Analysis of Income Potentials of Blocks Making Industry in Zamfara State, Nigeria (Lapai Journal of Economics, 2024)
The study is an analysis of the income potentials of blocks making industry in Zamfara state. The research employs the used primary sources of data, whereby the data was obtained from the responses of 100 blocks making industry entrepreneurs in the study area, who were selected with the aid of simple random sampling method. Descriptive and inferential statistics were employed for data analysis thus, multiple regression analysis using OLS model. The findings revealed that, blocks industry has potentials to generate income in the study area in other words, blocks making industry in Zamfara state has is an important tool for in terms of income generation, the study recommends among others that, in addition to the existing policy by government in supporting SMEs to get access to finance, more windows should be open by the Central bank of Nigeria, Bank of Industry and Commercial Banks to enable SMEs have more access to finance.